Histological Changes Induced by the Fusarium Graminarum Silver Nanoparticles in Some Organs of Male Albino Mice - Sahar A. H. AL-Sharqi (Indian Journal of Forensic Medicine & Toxicology, 2020)
The aim of this study was to investigate the effects on male albino mice of the histological change ofFusarium graminarum, silver nanoparticles (AgNPs), and the traces of these nanoparticles in the liver,kidney, and small intestinal. The experiment consisted of 40 mice divided into two groups, the first group of20 mice was considered to be the control animals and the other group was 21 days of treatment with a dose ofAgNPs (0.1ml / day). Microscopic examination of the liver showed disturbed structure of the hepatic lobule,hepatocyte hypertrophy with severs infiltration of inflammatory cells, kupffer cell proliferation, coagulates,necrosis and hydropic degeneration. In addition, the kidney section showed lobulated glomeruli, a large areaof hemorrhage, congested blood vessels that showed thickening in their walls, changes in degeneration andinflammatory cell infiltration.